Niveles de gallinaza y su efecto en la capacidad de carga del pasto Axonopus escoparius (maicillo verde) evaluados a la 6ta semana en Zungarococha - 2017 - Saldaña Rojas, Jose Misael (2019)
A work was developed in the Shop of Teaching and Investigation Garden Agrostologico of the Ability of Agronomy, where he/she thought about as objective to evaluate three gallinaza levels and its effects in the capacity of load of the grass green maicillo, the investigation was of experimental descriptive type, traverse of quantitative design, to achieve the objectives the statistical design of DBCA it was used with four treatments and three repetitions, the population conformed it 480 plants sowed in the area you/he/she experiences, the sample constituted it three plants for each experimental unit, being concluded in the following thing: according to the averages of the green matter the T3 (4 gallinaza kg/m2) it showed the best result about the capacity of load of the grass in study with 45 UGA/ha / to the 42 days of evaluation; according to averages of the other treatments in study the T2 and T1 are to also have for this reason them in consideration it will depend on the cost and readiness of the payment (gallinaza) since this organic material fluctuates its price and readiness according to times of campaign of the posture birds.